Integration of knowledge management system for the decommissioning of nuclear facilities - Yukihiro IGUCHI; Satoshi YANAGIHARA (Mechanical Engineering Journal, 2016)
The decommissioning of a nuclear facility is a long term project, handling information which begins from the design, construction and operation. Moreover, the decommissioning project is likely to be extended because of the lack of the waste disposal site especially in Japan. In this situation, because the transfer of knowledge and education to the next generation is a crucial issue, integration and implementation of a system for knowledge management is necessary in order to solve it. For this purpose, the total system of decommissioning knowledge management system (KMS) is proposed. In this system, we have to arrange, organize and systematize the data and information of the plant design, maintenance history, trouble events, waste management records etc. The collected data, information and records should be organized by computer support system e.g. data base system. It becomes a base of the explicit knowledge. Moreover, measures of extracting tacit knowledge from retiring employees are necessary. The experience of the retirees should be documented as much as possible through effective questionnaire or interview process. The integrated knowledge mentioned above should be used for the planning, implementation of dismantlement or education for the future generation.